2015
DOI: 10.3329/bmrcb.v40i2.25227
|View full text |Cite
|
Sign up to set email alerts
|

Fingerprints: A simple method for Screening Hemophilic Patients

Abstract: Background: The present study aims to compare hemophilic patients’ fingerprint types with the normal people to help diagnose the disease, particularly new occurrences of the disease. Method: This casecontrol study was conducted in 2012. Sixty two patients with hemophilia type A and 62 normal healthy people were selected. The type of fingerprint was determined by a forensic specialist who was kept unaware of the participants’ group. Using advanced Henry method, the main types of fingerprints were classified as … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 13 publications
0
1
0
Order By: Relevance
“…Some diseases reported correlating with fingerprint patterns such as down syndrome, mental retardation, multiple sclerosis, and thalassemia. 10 Raizada et al 11 researched dermatoglyphics to carcinoma breast patients in India to determine whether dermatoglyphics could be used for screening or guide future research for breast cancer. In their research, it found that there were significant dermatoglyphic differences between breast cancer patients and healthy people.…”
Section: Introductionmentioning
confidence: 99%
“…Some diseases reported correlating with fingerprint patterns such as down syndrome, mental retardation, multiple sclerosis, and thalassemia. 10 Raizada et al 11 researched dermatoglyphics to carcinoma breast patients in India to determine whether dermatoglyphics could be used for screening or guide future research for breast cancer. In their research, it found that there were significant dermatoglyphic differences between breast cancer patients and healthy people.…”
Section: Introductionmentioning
confidence: 99%